Application of sialic acid/polysialic acid in the drug delivery systems - Ting Zhang; Zhennan She; Zhenjun Huang; Jing Li; Xiang Luo; Yihui Deng (Elsevier, 2014)
The properties of modified biomaterial are gaining more and more importance in drug delivery systems. Sialic acid (SA) and polysialic acid (PSA) serve as endogenous substances, which are non-immunogenic and biodegradable. At the same time, SA modification of the drugs/carriers can enhance the uptake of tumor cell and retention in brain; PSA modification can reduce the immunogenicity of the proteins or polypeptides and increase circulation time of the modified drugs/carriers in the blood, thus achieving active targeting effect. These properties offer a variety of opportunities for applications in drug delivery systems. This article summarizes the biological functions of SA and PSA and presents the technologies of SA/PSA modified small molecule drugs, proteins and carriers in drug delivery systems.